Need for a reliable alternative to custom-made implant impression trays: An in vitro study comparing accuracy of custom trays versus specialized aluminum stock tray - Mukti Goel; Pankaj Dhawan; Piyush Tandan; Pankaj Madhukar (Wolters Kluwer Medknow Publications, 2018)
Purpose: The aim of the present study was to evaluate and to compare the accuracy of implant casts obtained by open tray pick-up impression technique using 2 types of custom-made trays and a specialized aluminum stock impression tray. Materials and Methods: A heat-cure acrylic resin master model was fabricated. Two implants were placed parallel to each other. Ten impressions were made from each group. Polyvinylsiloxane impression material with single step putty wash technique was used for making all the impressions. The resultant casts obtained were compared to the master models with respect to the distances measured between the reference points using a stereomicroscope. The data obtained was statistically analyzed using one-way ANOVA, Tukey's post hoc procedures, and t-test. Results: Mean value obtained was 2.012967 cm (±0.007060) for corimplant stock tray, 2.012627 cm (±0.007945) for autopolymerizing acrylic resin tray, 2.010279 cm (±0.006832) for light-cure hybrid composite tray. P value was calculated to be> 0.05; hence, there was nonsignificant deviation of observations from standard value in each group. Conclusion: Statistically insignificant difference was found between the accuracy of casts obtained by the different impression trays. However, light-cure hybrid composite trays showed best results followed by autopolymerizing acrylic resin trays and Corimplant stock tray.